Penerapan Permainan Monopoli Dalam Pembelajaran IPS Sebagai Media Belajar Bagi Siswa Di Sekolah Dasar - Maulida Dwi Susanti; Mega Ulia Putry; Sifaniar Harya; Susilawati Susilawati (Program Studi PGSD Kampus UPI di Serang, 2021)
Learning media is one of the important things in the learning process so that the learning process can be achieved and improve student learning outcomes. This study aims to analyze the application of social studies learning by using monopoly games as a medium of learning in elementary schools. The method chosen is literature study. First, the researcher determined the formulation of the problem, then continued to look for previous research data that already existed on Google Scholar relating to the Application of Monopoly Games with Social Studies Learning for Students in Elementary Schools. The results of the study were analyzed using the literature study method by looking for improvements during the cycle. Based on the results of the analysis of research data collection that the application of social studies learning by using monopoly games as learning media for students in elementary schools can improve student learning outcomes with the smallest percentage of 5% and the largest 40%.